"[It] does not explain everything … , nor does it explain nothing … it explains some things": Australia's first female Prime Minister and the dilemma of gender. (February 2019) - Sorrentino, Jasmin; Augoustinos, Martha; Le Couteur, Amanda
Despite advances in the representation of women in positions of leadership, gender-based inequalities persist. A particular dilemma for female leaders concerns whether to acknowledge, or avoid talking about, their experiences of gender and gender inequality in public life. Routinely, women who confront such discrimination experience social and personal repercussions; however, those who remain silent are often criticised for failing to support women. This article takes a discursive psychological approach to accounts from Australia's first female Prime Minister of the role of gender in her leadership. Following her controversial 'Sexism and Misogyny' speech in the Australian parliament (2012), Julia Gillard addressed this topic repeatedly in public interviews and speeches, and these materials constitute the data for analysis. We describe the complex and flexible nature of the discursive work required in navigating topics of gender and discrimination, looking in detail at how Gillard routinely accounted for gender as relevant – or not – to her political leadership, and how her identity was constructed as part of that process.